PENGEMBANGAN MEDIA AUDIO VISUAL BERBASIS DISCOVERY LEARNING PADA PEMBELAJARAN TEMATIK TERPADU DI KELAS IV SEKOLAH DASAR - Irma Suryani, Ade; Gemini Putri, Sesvina (Jurnal Riset Pendidikan Dasar Dan Karakter, 2024)
This research was motivated by the suboptimal use of audiovisual media in schools, which has not effectively motivated students. The media used were mostly downloaded YouTube videos, which did not enhance students’ creativity and active learning. Therefore, an audiovisual learning media based on the Discovery Learning model was developed for fourth-grade thematic learning at SDN 12 Sungai Liku, focusing on Theme 4, Sub-theme 1, Lessons 1, 2, and 3. This study employed a research and development (R&D) approach using the 4-D model (define, design, develop, disseminate). Instruments used included validation sheets and questionnaires for teacher and student responses. Validation results showed high validity: content (84.32%), design (96.87%), and language (89.28%). Teacher responses indicated a practicality level of 91% (very practical), while student responses reached 72% (practical). Thus, the developed audiovisual media is appropriate for use in integrated thematic learning for fourth-grade elementary students.